Carbon Trading as a New Paradigm for Indonesia's Polluter Pays Principle - Erwin Syahruddin; Rahmat Saputra; Andre Cardenas; Alizah Ali (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
Climate change is driven by a combination of natural fluctuations and human activities, particularly the widespread use of fossil fuels (such as coal, oil, and natural gas) and alterations in land use practices such as logging, farming, and clearing land for agriculture. This global phenomenon encompasses various end-of-use activities, including agriculture, forestry, and consumerism. An inherent challenge in the global carbon dioxide (CO2) trading landscape lies in the competition between developed and developing countries, stemming from inconsistent CO2 prices. This competition manifests in three primary areas. Firstly, in the context of internationally transmitted mitigation outcomes, involving international trade aimed at surpassing Nationally Determined Contributions (NDC) targets. Secondly, it pertains to sustainable development mechanisms, specifically the use of carbon offsets derived from projects implemented by both public and private entities worldwide. The third aspect revolves around non-market approaches, encompassing emission reduction through mitigation and adaptation efforts, financial support, technology transfer, and capacity building, which may involve tools like carbon taxes and Carbon Border Adjustment Mechanism (CBAM). This research adopts a legal norm perspective, delving into methods that investigate, describe, synthesize, interpret, evaluate, and analyze positive approaches. The findings signify a paradigm shift aligning with the